Corrosion prevention for Al2O3/SiC/C/MgAl2O4 based ceramics by means of impregnation with cerium-carrying solution - Justus, Sergio Murilo; Silva, Sidiney Nascimento; Vernilli, Fernando; Andrade, Ricardo Magnani [UNESP]; Matta, Gustavo Schemin da [UNESP]; Longo, Elson [UNESP]; Baldo, João Batista; Varela, José Arana [UNESP] (My University, 2010)
A cerium-carrying solution was developed so as to aprtially fill the open porosity of Al2O3/SiC/C/MgAl2O4 based refractory lining microstructure used in torpedo ladles, thereby enhancing wear resistance. The protection mchanism was cleared up and introduced from the impregnation technique using a cerium-carrying solution.